Respuesta :
Using function concepts, it is found that the correct options are:
I and III only
--------------------------------
The function is:
[tex]y = \frac{4}{x^2 - 4}[/tex]
--------------------------------
Statement 1:
A function is even if: [tex]f(x) = f(-x)[/tex]
We have that:
[tex]f(x) = \frac{4}{x^2 - 4}[/tex]
[tex]f(-x) = \frac{4}{(-x)^2 - 4} = \frac{4}{x^2 - 4} = f(x)[/tex]
Since [tex]f(x) = f(-x)[/tex], the function is even, and the statement is true.
--------------------------------
Statement 2:
The function increases when: [tex]f^{\prime}(x) > 0[/tex]
The derivative is:
[tex]f^{\prime}(x) = \frac{-8x}{(x^2-4)^2}[/tex]
The denominator is always positive, but the numerator can be both positive/negative, which means that when the numerator is negative(x > 0), the derivative will be negative, thus the function will decrease and the statement is false.
--------------------------------
Statement 3:
A horizontal asymptote is given by:
[tex]y = \lim_{x \rightarrow \infty} f(x)[/tex]
In this question:
[tex]y = \lim_{x \rightarrow \infty} \frac{4}{x^2 - 4} = \frac{4}{\infty - 4} = \frac{4}{\infty} = 0[/tex]
y = 0 is the x-axis, thus, the statement is true, and the correct option is:
I and III only
A similar problem is given at https://brainly.com/question/23535769